Removal of Methylene Blue from Aqueous Solutions using Chemical Activated Carbon Prepared from Jackfruit (Artocarpus heterophyllus) Peel Waste - Tengku Hasbullah, T.N.A; Selaman, O.S; Rosli, N.A (Universiti Malaysia Sarawak (UNIMAS), 2014)
Dye wastewater generated is rated as the most polluting wastewater among all the industrial sectors. Adsorption using activated carbon (AC) has been proven to be effective to treat dye wastewater. In this study, jackfruit (Artocarpus heterophyllus) peel waste has been utilized for activated carbon (AC) preparation using chemical activation. This research attempts to study the factors affecting its adsorption performance. Series of experiments conducted consisted of the experiments studying the effect of initial dye concentration and also effect of adsorbent dosage. In the study, CAC showed adsorption capacity of 10.43 mg/g.